Valorization of spent fluorescent lamp waste glass powder as an activator for eco-efficient binder materials. (17th October 2022) - Ali, Hafiz Asad; Lu, Jian Xin; Sun, Keke; Poon, Chi Sun
Graphical abstract: Highlights: Use of spent fluorescent lamp waste glass was investigated. Alternative activators were successfully synthesized using this waste glass. These activators had similar effects to the commercial activator in producing AAM. A recycling route for hazardous e-waste was preliminary demonstrated. Abstract: Spent fluorescent lamp waste glass is considered hazardous and requires an appropriate management and recycling route. Due to its highly alkali-siliceous nature, the feasibility of using the powdered form of the fluorescent lamp waste glass (FGP) to synthesize an activator for activating the GGBS/FA blend was studied. Additionally, the solubility and reactivity of FGP were compared with waste beverage bottle glass powder (BGP). Results showed that FGP had a higher solubility and reactivity than BGP due to the presence of the higher network modifiers. A significant enhancement in solubility (about 19 %), total heat release (57 – 62 %), and compressive strength (85 – 89 %) was observed in FGP-based mixtures, implying its suitability for activator design. The mechanical and microstructural properties of the alkali-activated pastes (AAP) prepared with the FGP activators were similar to those prepared with the commercially sourced reference activator. Before activator preparation, washing FGP with water or acid enhanced the availability of soluble silicates. The activators prepared with those washed FGP accelerated the alkali-activation process and helped achieve better strengths for the corresponding AAP. Their 28-day compressive strength values were in the range of 36 – 40 MPa and comparable to the control (FGP-C). In addition, the microstructural analysis showed that the reaction products in these mixtures were of C-(N)-ASH gels type with high Si/Al and low Ca/Si ratios. Thus, a recycling route for spent fluorescent lamp waste glass was preliminary demonstrated in this study.